Interdisciplining Digital Humanities: Boundary Work in an Emerging Field - T Klein, Julie (Digital Humanities, 2015)
The first book to test the claim that the emerging field of Digital Humanities is interdisciplinary and also examines the boundary work of establishing and sustaining a new field of study